(untitled) (Research, Society and Development, 2025)
This study addresses emotional support in highly complex environments: the role of the psychologist in the ICU. The objective is to investigate how the psychologist’s role in the ICU contributes to the humanization of care, promoting emotional support and management of psychological distress. Methodology: this is an integrative systematic review, based on the chosen articles, the results were analyzed and discussed. Following the inclusion criteria: articles in Portuguese and English were considered, related to the topic addressed, establishing the time frame of the last five years (2020 to 2024). The exclusion criteria are: studies that did not address the topic in question, such as monographs, course completion works, abstracts and those that were not in full. Works with a publication date prior to the time frame established for the research were also discarded. From this, 7 articles were selected from the Google Scholar database and CAPES journal. In conclusion, the psychologist’s role in the ICU contributes to the humanization of care, promoting emotional support for patients and family members admitted to the Intensive Care Unit (ICU), an environment that generates emotional states capable of impacting the evolution of the patient’s clinical condition.